Penyuluhan Kesehatan tentang Menstruasi dan Permasalahannya pada Remaja Putri di SMP Negeri 2 Kecamatan Peusangan Siblah Krueng - Sri Raudhati; Agustina Agustina; Irma Fitria (Jurnal Abdimas Kesehatan (JAK), 2023)
Menstruation is still a taboo subject to be discussed by people in several parts of Indonesia. The Indonesian Demographic and Health Survey in 2017 indicated that 1 in 5 young women had never discussed menstruation with adults before experiencing menarche. In fact, cleanliness and maintenance of reproductive organs during menstruation is very important to avoid various menstrual problems. The purpose of this community service is so that young women are able to understand how to fulfill the health of their reproductive organs. This activity is oriented towards 30 young women of SMP Negeri 2 Siblah Krueng, Bireuen Regency. The methods used in providing menstrual education are lectures, material presentations, leaflet distribution, and videos. Evaluation of this activity is by holding a discussion group during the activity. The results obtained from community service indicate that there is a clear understanding of female students, which can be seen in the evaluation stage of menstrual education counseling. Young women were very enthusiastic during the discussion by actively providing responses and questions. The counseling methods and media used in this community service can effectively increase young women's understanding of menstrual health. The school will disseminate information about menstrual health not only for young women but also for young men, so that menstrual health is no longer taboo and can be discussed openly for certain purposes.